CURRENT STATUS OF FUNCTIONAL FOODS RESEARCH AND DEVELOPMENT IN INDONESIA: OPPORTUNITIES AND CHALLENGES - Indah Purwaningsih; Ria Hardiyati; Muhammad Zulhamdani; Chichi Shintia Laksani; Yan Rianto (Jurnal Teknologi dan Industri Pangan, 2021)
The development of functional foods requires extensive research and development (R&D) activities for product development, technology development and commercialization. However, it becomes rather a complex issue in developing countries, including Indonesia. This study briefly discusses the status of functional foods R&D in Indonesia by understanding the opportunities and challenges. Employing scientometrics with bibliometric data from Scopus Database from the early retrievable date to October 29, 2018, the study finds out that R&D on functional foods in Indonesia indicates a substantially increasing trend in the last decade. The research activities are mostly conducted by public research institutes (PRIs) and universities in the area of identification of bioactive compounds and their effects on health. They explore the abundant potentially indigenous biodiversity from Indonesia, both land and marine resources. Nonetheless, the R&D activities are still lacking of network and integration between the subject areas. Underdeveloped infrastructure, limited human resources and financial support, costly preparation for the clinical test to satisfy health claims regulation and the gap between academic research and industry have been key issues in Indonesian functional foods R&D. By using innovation system perspectives, this study suggests that public R&D on functional foods demands active collaboration between PRIs, universities and industry as well as the supportive regulation system from policymakers to enhance the development of functional foods in the future.